2016
DOI: 10.1016/j.jhep.2016.02.040
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive androstane receptor (Car)-driven regeneration protects liver from failure following tissue loss

Abstract: The unique regenerative capacity of liver has its natural limits. Following tissue loss that is too excessive, such as through extended resection in the clinic, liver failure may develop. This is known as small-for-size-syndrome (SFSS) and represents the most frequent cause of death due to liver surgery. Here we show that deficient induction of the protein Car, a central regulator of liver function and growth, is a cause of liver failure following extended resection; reactivation of Car through pharmacological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 29 publications
4
71
0
Order By: Relevance
“…α Hif2a small interfering RNA (siRNA) and control siRNA were designed and validated by Axolabs Gmbh (Kulmbach, Germany) and packed into company‐owned formulations preferentially targeting murine hepatocytes. We have confirmed preferential targeting in regenerating hepatocytes . Aha1 was chosen as an internal control knockdown because it does not yield any phenotype in vivo (Axolabs, personal communication) and has no apparent impact on liver regeneration .…”
Section: Methodsmentioning
confidence: 99%
“…α Hif2a small interfering RNA (siRNA) and control siRNA were designed and validated by Axolabs Gmbh (Kulmbach, Germany) and packed into company‐owned formulations preferentially targeting murine hepatocytes. We have confirmed preferential targeting in regenerating hepatocytes . Aha1 was chosen as an internal control knockdown because it does not yield any phenotype in vivo (Axolabs, personal communication) and has no apparent impact on liver regeneration .…”
Section: Methodsmentioning
confidence: 99%
“…Tgr5 enhances bile salt elimination in urine, reduces bile salt hydrophobicity and prevents excessive cytokine production by Kupffer cells, in case of bile salt overload [14]. Other nuclear receptors that play a direct role in liver regeneration, and have the potential to reduce intrahepatic bile salt toxicity by promoting phase I/II metabolism, are the pregnane X receptor and constitutive androstane receptor [157,158]. A recent study showed that the pregnane X receptor agonist rifampicin improved hyperbilirubinemia and clinical status in patients with persistent hepatocellular failure, including one patient with PLF [159].…”
Section: Regenerative Interventionsmentioning
confidence: 99%
“…Tschuor et al 4 explored the mechanisms involved in liver regeneration, especially the role of Nr1i3 (constitutive androstane receptor, CAR) in mice models. CAR plays a role in detoxification of endo-and xenobiotics.…”
Section: Commentarymentioning
confidence: 99%